Existence and stability results for ψ-Caputo fractional integrodifferential equations with delay - D, Prabu (KOMUNITAS Analisis Matematika INDONESIA, 2024)
This paper deals with the existence and uniqueness results for ψ-Caputo fractional integrodifferential equations with finite delay. The results are obtained by using the standard fixed point theorems. An example is given to show the main discoveries.